As indagações cotidianas de jovens indígenas Potĩgûara-PB no currículo de filosofia no ensino médio - Silva, Rosemary Marinho da (2019)
This Thesis starts by noting that the contents listed in the National Curriculum Guidelines for High School, which also guides the production of textbooks and the construction of state curricula, are centered on European Philosophy as universal Philosophy, taught to young Brazilian students, among those, young indigenous students. Without denying the contribution of European philosophy, this work points out the problem that the reproduction of a single way of doing philosophy, through the teaching of a European philosophy as the only philosophical tradition, implies the persistence of the colonization process, the silencing, and the erasure of ethnic identity of Brazilian indigenous peoples and, consequently, the reinforcement of the epistemicide suffered by those peoples. For this reason, it is argued that only by listening to indigenous peoples, among those, their youth, that there could be a production of inquiries, coming from their daily life, which could be configured as a permanent exercise of philosophical inquiry. Questioning is then understood as a first moment of philosophizing, because it is a process of estrangement, distancing and questioning of daily life. But how can indigenous youngsters find their daily life strange and express their questions so that they can compose a proposal of curriculum contents for the Teaching of Philosophy in High School that broadens the contents already present in the Philosophy curriculum? This central question required three assumptions: young indigenous people are able to reflect on their daily lives, to problematize their reflections and conceptions, and through this process of reflection and problematization, to propose contents to be studied in the teaching of philosophy in high school. Therefore, a general objective was established: to highlight the daily inquiries of young Potiguara-PB high school students, at Professor Luiz Gonzaga Burity Integral Technical School, in Rio Tinto / PB, within their interfaces with the Philosophy curriculum in high school. To do so, the concepts of youth, youth protagonism, intraculturality and interculturality, identity and curriculum were defined as a theoretical field. The empirical field was Professor Luiz Gonzaga Burity Technical Integral Citizen School, located in the city of Rio Tinto, a non-indigenous school, surrounding the Potĩgûara territory, in Paraíba State, as a fruitful place for collecting inquiries from young Potĩgûara - students. The methodological choices were based on the qualitative approach, using the Intervention Research method that gathered the following strategies: participant observation, semi structured interviews, pedagogical workshops and focus group. The analysis of the collected data was performed through the Discursive Textual Analysis. Therefore, the Thesis expresses the need for an intercultural curriculum for the Teaching of Philosophy in High School, with which an open and plural dialogue between indigenous and non-indigenous knowledge should be established, self-valued and affirmed as places of construction of philosophical and educational concepts and knowledge. The Thesis is configured as a curricular proposal that points out nine curricular contents, elaborated, collaboratively, with young Potĩgûara-PB indigenous peoples, as an intercultural landmark in the Teaching of Philosophy in High School.